Taxonomy and biological aspects of the Central American cichlid fishes Cichlasoma sieboldii and C. tuba - Bussing, William A. (1975)
The complex taxonomic history of Cichlasoma sieboldii is reviewed. Cichlasoma punctatum and its synonym Theraps terrabae are included for the first time in the synoymy of C. sieboldii. A report of C. guttulatum from Panamá is attributable to a misidentification of C. tuba, which had not been previously reported from that country.The morphologic and meristic variation, coloration, ecology and geographic distribution of C. sieboldii and C. tuba are discussed. Morphologic and distributional evidence suggest that these two species are Pacific and Atlantic slope derivatives of a common Pliocene ancestor.